SoC control for improved battery life and throughput performance under VST‐TDMA. Issue 3 (1st February 2017) - Torres, Boris; Quintero, Vanessa; Estevez, Claudio; Orchard, Marcos; Azurdia, César
Abstract : Energy independence is a wireless device quality that demands the utmost exigency. Energy harvesting devices (EHD) alleviate the energy constraints demanded by these nodes and with the use of protocols, such as variable slot time‐time division multiple access (VST‐TDMA) energy self‐sustainability can be attained at the cost of throughput. To allow high throughput levels and self‐sustainability the system can allow the power consumption to be greater than the energy harvesting rate while a state‐of‐charge (SoC) of 30% or greater is maintained. To achieve this the system must accurately estimate the SoC, which is not a trivial task. In this work, a battery model is incorporated into the VST‐TDMA protocol to estimate the battery model parameters, including the SoC, which successfully allows it to maintain appropriate SoC levels.